Lectotypification of six names in Phyllantheae Dumort. (Phyllanthaceae) - Torres, Alícia Marques [UNESP]; Athiê-Souza, Sarah Maria; Pereira-Silva, Rafaela Alves; de Sales, Margareth Ferreira (Springer Nature, 2022)
As a part of the study of Phyllanthaceae for the Atlantic Forest in northeastern Brazil, as well as the genus Phyllanthus in the flora of Brazil, six lectotypes are proposed for the following Müller Argoviensis accepted binomials: Flueggea schuechiana, Phyllanthus avicularis, P. bahiensis, P. lindbergii, P. minutulus and P. poeppigianus.
Keywords: Brazil; Flueggea; lectotype; Phyllanthus